Hardware-Efficient Stochastic Binary CNN Architectures for Near-Sensor Computing - Parmar, Vivek; Penkovsky, Bogdan; Querlioz, Damien; Suri, Manan (Frontiers in Neuroscience, 2022)
With recent advances in the field of artificial intelligence (AI) such as binarized neural networks (BNN), a wide variety of vision applications with energy-optimized implementations have become possible at the edge. Such networks, have the first layer implemented with high-precision which poses a challenge in deploying a uniform hardware mapping for the network implementation. Stochastic computing can allow conversion of such high-precision computations to a sequence of binarized operations while maintaining equivalent accuracy. In this work, we propose a fully binarized hardware-friendly computation engine based on stochastic computing as a proof of concept for vision applications involving multi-channel inputs. Stochastic sampling is performed by sampling from a non-uniform (normal) distribution based on analog hardware sources. We first validate the benefits of the proposed pipeline on the CIFAR-10 dataset. To further demonstrate its application for real-world scenarios, we present a case-study of microscopy image diagnostics for pathogen detection. We then evaluate benefits of implementing such a pipeline using OxRAM-based circuits for stochastic sampling as well as in-memory computing based binarized multiplication. The proposed implementation is about 1,000 times more energy-efficient compared to conventional floating-precision based digital implementations, with memory savings of a factor of 45.